Enamel hypoplasia of the primary dentition in a 4-year-old with intestinal lymphangiectasia - P. ARROW (Paediatric Dentistry, 2005)
Intestinal lymphangiectasia (IL) is a rare disorder, and its incidence and prevalence is unknown for either Australia or world-wide.